STRATEGI GURU DALAM MENDIDIK AKHLAK PESERTA DIDIK DI SEKOLAH DASAR - Fitriani Fitriani; Yola Lestari; Japeri Japeri; Silva Namira; Engkizar Engkizar; Fuady Anwar (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
This research is aimed to find the teachers‘ strategies in educating the student’s moral in primary school. The research used a qualitative method with the case study approach. The research data source was gotten by doing the interview, using a set interview protocol with fifteen respondents-the teacher of Islamic education, Quran teacher and the students. The data was analyzed thematically by using the software qualitative Nvivo 12. Overall, the results of the research got five themes relate to the teachers‘strategies in educating morals, such as: Conducting weekly lectures, Set a good example at the school, Giving advice to the students individually, Teach the moral lesson at the school, and Giving a warning and punishment to the students that doing the bad thing. All of those strategies was done by the teachers based on the result of this research. It can be a reference to others in educating students‘moral.